1995
DOI: 10.1007/bf00222971
|View full text |Cite
|
Sign up to set email alerts
|

Identification of chrysanthemum cultivars and stability of DNA fingerprint patterns

Abstract: Several techniques of DNA analysis were applied to identify chrysanthemum cultivars. Unrelated cultivars could be distinguished by using RAPDs (random amplified polymorphic DNAs), inter-SSR (simple sequence repeat) PCR (polymerase chain reaction), hybridization-based DNA fingerprinting, as well as RFLPs (restriction fragment length polymorphisms). Cultivars with different flower colours and belonging to one family, i.e. vegetatively derived from 1 cultivar, appeared to have the same DNA fragment patterns, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
1
4

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(47 citation statements)
references
References 38 publications
0
41
1
4
Order By: Relevance
“…The characterization of chrysanthemums is vital for their conservation and management as well as for the understanding of their genetic relationships. Several DNA works and genetic studies have investigated the chrysanthemum using different molecular markers, such as RAPDs (Wolff et al, 1995;Chatterjee et al, 2006;Zhang et al, 2010b), sequence-characterized amplified regions (Chatterjee et al, 2006), chloroplast SSR markers (Yang et al, 2006), amplified fragment length polymorphisms (Zhang et al, 2010b), and sequence-related amplified polymorphisms (Zhang et al, 2011). However, the results based on morphology, cytology, interspecific hybridization, and molecular systematics have indicated that a lot of work remains to be done on chrysanthemums (Silan et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characterization of chrysanthemums is vital for their conservation and management as well as for the understanding of their genetic relationships. Several DNA works and genetic studies have investigated the chrysanthemum using different molecular markers, such as RAPDs (Wolff et al, 1995;Chatterjee et al, 2006;Zhang et al, 2010b), sequence-characterized amplified regions (Chatterjee et al, 2006), chloroplast SSR markers (Yang et al, 2006), amplified fragment length polymorphisms (Zhang et al, 2010b), and sequence-related amplified polymorphisms (Zhang et al, 2011). However, the results based on morphology, cytology, interspecific hybridization, and molecular systematics have indicated that a lot of work remains to be done on chrysanthemums (Silan et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…High levels of polymorphisms at the DNA level in chrysanthemums have been determined (Wolff and Peters-Van Rijn, 1993), and Wolff et al (1995) found identical DNA patterns in different accessions of the same chrysanthemum cultivar using random amplified polymorphic DNA (RAPD). Huang et al (2000) detected molecular markers in three hybrid combinations of chrysanthemums using RAPD, and they were able to select 22 primers of the 45 random primers screened.…”
Section: Introductionmentioning
confidence: 99%
“…In ornamental species ISSRs have been used in Jacaranda sp (Pérez de la Torre et al 2003;Escandón et al 2005a), Nierembergia (Escandón et al 2005b), Pandorea sp (Jain et al 1999) and Chrysantemum (Wolff et al 1995). The ISSR strategy was applied to generate fingerprints in selected clones of N. linariaefolia, supported by the reproducibility of the banding patterns compared to the RAPD's ones, being the longer primers and the higher annealing temperature the probable causes of this difference (Nybon, 2004).…”
Section: )mentioning
confidence: 99%
“…Características atrativas como a possibilidade de se obter um grande número de marcadores genéticos sem qualquer informação prévia sobre seqüências de nucleotídeos do genoma da espécie, o baixo custo, rapidez, simplicidade e velocosdade na aquisição dos dados (Ferreira & Grattapaglia, 1996), levaram os pesquisadores a utilizar amplamente o método, especialmente em análises filogenéticas, "fingerprinting" e mapeamento genômico, empregado-o muitas vezes como uma panacéia na busca de marcadores moleculares. Sendo indicado como um método possivelmente importante em programas de identificação de cultivares (Weeden, 1992;Ko et al, 1994;Multani & Lyon, 1995;Smith, 1995e Smith & Register, 1998, várias tentativas têm sido feitas buscando a sua adaptação para esse fim (Beyermann et al, 1992;McDonald et al, 1994;Ko et al, 1994;Mailer et al, 1994;Multani & Lyon, 1995;Wolff et al, 1995;McDonald, 1995;Gallego & Martinez, 1996;Jianhua et al, 1996a-b;Ford & Taylor, 1997;Meng et al, 1998;Marcos-Filho & McDonald, 1998;Meng et al, 1998e Noli et al, 1999. No entanto, parece que a simplicidade da técnica tem obscurecido a necessidade de dar significado aos produtos gerados.…”
Section: Introductionunclassified
“…Ainda, um grande nú-mero de outros trabalhos mostra a utilização de RAPDs para identificação de cultivares de diferentes espécies. Podemos citar, por exemplo, girassol (Lawson et al, 1994), banana (Kaemmer et al, 1992e Howell et al, 1994, aipo (Yang & Quiros, 1993), couve-flor e brócolis (Hu & Quiros, 1991e Kresovich et al, 1992, mamão (Stiles et al, 1993), coco (Wilde et al, 1992), cebola (Wilkie et al, 1993), algodão (Iqbal et al, 1997), cevada (Schut et al, 1997), milheto (Chowdari et al, 1998), petúnia (Cerny et al, 1996), groselha-negra (Ribes nigrum L.) (Lanham et al, 1995), crisânte-mo (Wolff et al, 1995), Mangifera indica L. (Schnell et al, 1995), trigo (He et al, 1992), mandioca (Colombo et al, 1998), tomate (Noli et al, 1999), batata (Ford & Taylor, 1997), milho e soja (Jianhua et al, 1996a). Apesar de todas essas aproximações no sentido de adaptar a técnica de RAPD para a identificação de cultivares, a pesquisa não tem dirigido a atenção necessária para explicar as causas básicas do polimorfismo no padrão de bandas, resultando em estimativas muito inconsistentes.…”
Section: Introductionunclassified